The Impact of Cybercafes on the Connectedness of Children Left Behind by Overseas Filipino Workers - Alampay. Erwin A.; Alampay, Liane P.; Raza, Khane S. (Diliman, Quezon City, Philippines National College of Public Administration and Governance, 2013)
This study looks at the use of cybercafes by children of overseas Filipino workers (OFWs). It determines how cybercafes function as an alternative to home internet access in terms of the internet's function to maintain familial connectedness.
Global Impact Study Research Report Series 2013
Keywords: Internet and children